Compatibility Evaluation and Anatomical Observation of Melon Grafted Onto Eight Cucurbitaceae Species - Xiong, Mu; Liu, Changjin; Guo, Liping; Wang, Jin; Wu, Xiangshuai; Li, Ling; Bie, Zhilong; Huang, Yuan (Frontiers in Plant Science, 2021)
Melon (Cucumis melo) is one of the top ten fruits in the world, and its production often suffers soil-borne diseases. Grafting is an effective way to solve this problem. However, incompatibility between scion and rootstock limits the application of melon grafting. Here, melon was grafted onto 8 Cucurbitaceae species (cucumber, pumpkin, melon, luffa, wax gourd, bottle gourd, bitter gourd, and watermelon), graft compatibility evaluation and anatomical observation were conducted. Taking melon homo-grafted plants as control, melon grafted onto cucumber and pumpkin rootstocks was compatible, and it was incompatible of melon grafted onto luffa, wax gourd, bottle gourd, bitter gourd, and watermelon rootstocks based on the scion dry weight at day 42 after grafting. Meanwhile, we found that starch-iodine staining of scion stem base is an index to predict graft compatibility earlier, at day 14 after grafting. Further microsection observations showed that there was more cell proliferation at graft junction of melon hetero-grafted combinations; vascular reconnection occurred in all graft combinations. However, excess callose deposited at graft junction resulted in the blockage of photosynthate transport, thus leading to the starch accumulations in scion stem base and finally graft incompatibility. In addition, undegraded necrotic layer fragments were observed at graft junction of melon grafted onto incompatible bitter gourd and watermelon rootstocks. The above results provide clues for the selection and breeding of compatible Cucurbitaceae rootstocks of melon, and demonstrate that starch accumulation in scion base and callose deposition at graft junction are associated with melon graft compatibility.